2004
DOI: 10.1088/1126-6708/2004/01/017
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solution of Quantum Field Theory on Noncommutative Phase Spaces

Abstract: We present the exact solution of a scalar field theory defined with noncommuting position and momentum variables. The model describes charged particles in a uniform magnetic field and with an interaction defined by the Groenewold-Moyal star-product. Explicit results are presented for all Green's functions in arbitrary even spacetime dimensionality. Various scaling limits of the field theory are analysed non-perturbatively and the renormalizability of each limit examined. A supersymmetric extension of the field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(202 citation statements)
references
References 74 publications
3
199
0
Order By: Relevance
“…Using direct space methods, we have provided a new proof of the BPHZ theorem for vulcanized non commutative φ 4 4 [47]. We have also extended the Grosse-Wulkenhaar results to theφ φ φ φ LSZ model [43]. Our proof relies on a multiscale analysis analogous to [42] but in direct space.…”
Section: Arxiv:07050705v1 [Hep-th] 4 May 2007mentioning
confidence: 94%
See 3 more Smart Citations
“…Using direct space methods, we have provided a new proof of the BPHZ theorem for vulcanized non commutative φ 4 4 [47]. We have also extended the Grosse-Wulkenhaar results to theφ φ φ φ LSZ model [43]. Our proof relies on a multiscale analysis analogous to [42] but in direct space.…”
Section: Arxiv:07050705v1 [Hep-th] 4 May 2007mentioning
confidence: 94%
“…This is just wrong but for a more subtle reason. We have shown that the Grosse-Wulkenhaar method can be extended to renormalize theories such as the Langmann-Szabo-Zaremboφ φ φ φ model [43,44,45] in four dimensions or the Gross-Neveu model in two dimensions. In these theories the ordinary Mehler kernel is replaced by a related kernel which governs propagation of charged particles in a constant background field.…”
Section: Arxiv:07050705v1 [Hep-th] 4 May 2007mentioning
confidence: 99%
See 2 more Smart Citations
“…The key to the renormalization of the duality-covariant model is the use of a "matrix basis" for the expansion of fields given by [17,21] …”
Section: Renormalization Of the Duality-covariant Field Theorymentioning
confidence: 99%